2019
DOI: 10.1108/whatt-08-2019-0049
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability communication in hospitality in peripheral tourist destinations

Abstract: Purpose The purpose of this study posited that tourism companies and more especially hotels located in tourist destinations dependent on air transportation, need to commit more strongly to sustainability because of their greater distance from the main outbound markets. The research focused on determining whether hotels’ star rating, location, age and size influence their sustainability communication and on identifying the characteristics of the messages used in hotels’ sustainability communication. Design/me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…It is believed that to reduce customer perceptions of greenwashing, hotels with low environmental performance exaggerate their green achievements and disclose more positive information about their green activities in comparison with hotels with high environmental performance (Koseoglu et al , 2021; Park et al , 2021). Therefore, some hotels deliberately hesitate to disclose their green initiatives, a phenomenon called “green hushing,” to avoid customer doubts regarding the disclosure of a hotel’s green information (Santos et al , 2019; Shen et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that to reduce customer perceptions of greenwashing, hotels with low environmental performance exaggerate their green achievements and disclose more positive information about their green activities in comparison with hotels with high environmental performance (Koseoglu et al , 2021; Park et al , 2021). Therefore, some hotels deliberately hesitate to disclose their green initiatives, a phenomenon called “green hushing,” to avoid customer doubts regarding the disclosure of a hotel’s green information (Santos et al , 2019; Shen et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…(Chan, 2013a; Iyer and Jarvis, 2019; Kim et al , 2017; Martinez et al , 2020; Yadav et al , 2016). Hotel green marketing attempts to trigger customers’ positive perceptions and beliefs about the green image of hotels, boost hotel green brand credibility and reduce customer suspicion regarding a hotel’s greenwashing (Chan, 2013a; Chen et al , 2018; Khatter et al , 2021; Kim and Roseman, 2022; Santos et al , 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the automated approach is used in this study to analyze contents communicated in official websites in relation to characteristics that the literature suggested may influence their persuasiveness. These include the communication of specific contents on topics relating to all the (environmental, economic, socio-cultural) sustainability dimensions [7,11,20] and the emotional appeal of contents [7,18,20].…”
Section: Methodsmentioning
confidence: 99%
“…Based on the analysis of Malaysian hotels, Joseph et al [17] found that websites are not fully utilized to create awareness about sustainable development and mostly report economic information, followed by social and environment sustainability information. In the same line, Santos et al [18] show that only a minority of hotels in Portugal explicitly practice sustainability communication, but they do it in a quite superficial way and using a rational appeal. With reference small and medium accommodation firms in the Azores, Tiago et al [19] concluded that digital communication could be substantially improved and is linked to website sophistication.…”
Section: Introductionmentioning
confidence: 97%
“…The last part of the questionnaire dealt with the respondents' sociodemographic characteristics, such as gender (Female and Male); age (≤30 years, >30 ≤ 50 years, > 50 years); geographical area of residence (Europe, Americas, Asia/Pacific, Africa and (Santos et al, 2019) AC5…”
Section: Survey Instrument and Validationmentioning
confidence: 99%